Basis of specificity for a conserved and promiscuous chromatin remodeling protein - Donovan, Drake A (eLife, 2021)
Eukaryotic genomes are organized dynamically through the repositioning of nucleosomes. Isw2 is an enzyme that has been previously defined as a genome-wide, nonspecific nucleosome spacing factor. Here, we show that Isw2 instead acts as an obligately targeted nucleosome remodeler in vivo through physical interactions with sequence-specific factors. We demonstrate that Isw2-recruiting factors use small and previously uncharacterized epitopes, which direct Isw2 activity through highly conserved acidic residues in the Isw2 accessory protein Itc1. This interaction orients Isw2 on target nucleosomes, allowing for precise nucleosome positioning at targeted loci. Finally, we show that these critical acidic residues have been lost in the Drosophila lineage, potentially explaining the inconsistently characterized function of Isw2-like proteins. Altogether, these data suggest an ‘interacting barrier model,’ where Isw2 interacts with a sequence-specific factor to accurately and reproducibly position a single, targeted nucleosome to define the precise border of phased chromatin arrays.